Exergy-economic based multi-objective optimization and carbon footprint analysis of solar thermal refrigeration systems - Amin Motevali Emami; Ehsan Baniasadi; Ahmed Rezk (Case Studies in Thermal Engineering)
The increasing carbon footprint associated with conventional cooling methods underscores the urgent need for sustainable alternatives. This study investigates the economic and environmental advantages of various solar-thermal cooling systems, with a focus on optimizing their performance across different climate conditions. Employing a multi-objective approach, the research emphasizes exergy-economic indices to optimize selected cycles. The analysis covers multiple refrigeration technologies, including liquid absorption, solid adsorption, and solid desiccant cycles. Results indicate that the liquid absorption cycle performs optimally in hot, arid climates, reducing the payback period to approximately 8 years when optimized. In hot and humid regions, the solid desiccant cycle proves most effective due to its superior humidity control, yielding a payback period of 5.3 years. For cold and mountainous areas, the solid adsorption cycle is preferred, with a payback period of 13.5 years, while moderate and humid climates benefit from the solid desiccant cycle for both cooling and humidity regulation. The exergy-economic factors for the solar refrigeration systems across semi-arid, hot and arid, hot and humid, cold and mountainous, and moderate and humid climates are 0.758, 0.602, 0.698, 0.74, and 0.575, respectively.